Poetry After the Invention of América Don’t Light the Flower - Ajens, A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
This collection of essays traces the emergence of the Western poem from the standpoint of its collision with "American" otherness, particularly, the Latin American tradition. Unlike works extending Western conceptions of writing or searching for an alleged American ethnopoetics, this book approaches literature as a Western invention and, in turn, seeks out correspondences between traditions.
Keywords: Literature .; Poetry; America—Literatures.; Postcolonial/World Literature; Poetry and Poetics; North American Literature